The Effect of Motivation And Job Satisfaction On Employee Performance (Study at PT.Jepe Press Media Utama) - Nur Hayati; Supartini; Novelia Asita Mranani (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2022)
Human resources are important assets that must be managed properly by the company in order to make an optimal contribution. Keeping employees motivated is very important because motivation underlies each individual to act and do something. With high work motivation, employees will be more active in carrying out their work. Companies need to commemorate motivation and job satisfaction by going through Training, Welfare, Work Motivation, Promotion, and Salary, Co-Workers, Bosses, Jobs, Work Environment, and targets, on time, quality of work used by the company. This type of research uses a quantitative approach with a type of correlation analysis research. Descriptive research does not provide treatment, manipulation, but describes a condition as it is. The research location was taken by all employees of PT Jepe Press Media Utama. Several indicators of the Effect of Motivation on Employee Performance, the Effect of Job Satisfaction on Employee Performance, and the Effect of Motivation and Job Satisfaction on Employee Performance. Based on the results of research that has been carried out, the variables of motivation and job satisfaction have a positive and significant effect simultaneously on the performance of PT. Jepe Press Media Main. This is based on the calculation results of the F test, by comparing F count and F table, it is obtained that F count (92.782) is greater than F table (3.115), and the significance value is 0.000 less than the significance level of 0.05.